2007
DOI: 10.1007/s11666-007-9099-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics of Al-Co-Ce Coatings Produced by the Cold Spray Process

Abstract: Gas atomized feedstock particles of an Al-13Co-26Ce alloy system were sprayed using the Cold Spray deposition technique. The microstructures of the coatings produced are examined and the mechanical characteristics, in particular the bending fatigue and the bond strength, of the Al-Co-Ce coatings are reported. The results show that the Al-Co-Ce coatings improved the fatigue behavior of AA 2024-T3 specimens when compared to uncoated and Alclad specimens. During the bond strength tests, the bonding agent failed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 32 publications
1
21
0
2
Order By: Relevance
“…Unfortunately, there is very limited published literature on the fatigue behavior of cold-sprayed coatings [21][22][23]. Price et al have reported a decrease in fatigue resistance of Ti6Al4V alloy substrates when cold sprayed with pure titanium, and argued that the decrease may be explained by substrate-coating interface properties [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, there is very limited published literature on the fatigue behavior of cold-sprayed coatings [21][22][23]. Price et al have reported a decrease in fatigue resistance of Ti6Al4V alloy substrates when cold sprayed with pure titanium, and argued that the decrease may be explained by substrate-coating interface properties [22].…”
Section: Introductionmentioning
confidence: 99%
“…Price et al have reported a decrease in fatigue resistance of Ti6Al4V alloy substrates when cold sprayed with pure titanium, and argued that the decrease may be explained by substrate-coating interface properties [22]. Sansoucy et al [23] studied the influence of Al-Co-Ce alloy cold spray coating on the fatigue life of 2024 aluminum alloy substrate, and found notable improvement in the fatigue endurance limit. It was suggested that the increase in the fatigue behavior was attributed to the residual compressive stresses and to high bonding strength of the coatings to the substrate [23].…”
Section: Introductionmentioning
confidence: 99%
“…On particle impact with the substrate, the high kinetic energy of the particles results in severe plastic deformation and the creation of a deposition layer. CS coatings typically show high bond strength and excellent mechanical characteristics, including metals of strong engineering interest such as aluminium, titanium and their alloys [6,7,8,9]. The deposition of thermoplastic powder has also been achieved onto metallic and non-metallic substrates [10].…”
Section: -Introductionmentioning
confidence: 99%
“…В результате экспериментов были успешно нанесены покрытия практически из всех типов металлов (Al, Cu, Zn, Mo, Ta, Ti, Cr, Nb, Zr, Ag, Fe и многих других) и сплавов, широко применяющихся в промышлен-ности [16][17][18][19][20][21][22][23]. В качестве обобщающих характе-ристик ХГН покрытий можно выделить: 1) низкое в сравнении с другими способами порошкового напыления содержание оксидов;…”
Section: т 16 № 2 с 106-112unclassified